Chemical compositions and Anti-malassezia properties of Vietnamese Mentha arvensis and Piper betle essential oils - Vu, T. X.; Tran, T. B.; Hoang, C. Q.; Nguyen, H. T.; Phan, M. X. B.; Dao, A. N.; Dinh, M. T.; Soytong, K.; Nguyen, H. Q. (International Journal of Agricultural Technology, 2021)
Malassezia species causes serious diseases in immuno-incompetent or immuno-compromised hosts. Synthetic antifungal agents can treat Malassezia-associate disorders. However, the hypersensitivity, toxicity, and resistance to the synthetic drugs due to their improper use are raising public concerns. Thus, the safer antifungal agents are actively seeking. Plant essential oils are natural defenders which protect their hosts from both biotic and abiotic attacks. Several essential oils have been shown to inactivate Malassezia spp. in vitro and to fight Malassezia-associated diseases in vivo. Essential oils from Mentha arvensis and Piper betle plants have been widely used in Vietnam and demonstrated to kill a variety of bacteria and fungi. Nevertheless, their inhibitory effects against Malassezia species have not been evidenced. In this study, essential oils yielded from M. arvensis and P. betle plants cultivated in Vietnam were 1% (0.9% - 1.09%) and 0.25% (0.2% - 0.3%), respectively. M. arvensis oil contained 11 compounds, of which menthol (68.19%) and menthone (22.77%) were the two major molecules. Eugenol acetate (38.66%), and m-eugenol (30.28%) were the most abundant compounds in P. betle essential oil. Agar diffusion method showed that M. arvensis and P. betle essential oils inhibited the growth of Malassezia. furfur (ATCC 14521 and VNF01) and Malassezia globosa (VNG02) by ~ 100% and ~ 40%, respectively. Agar dilution assays identified 2.5 µl/ml and 1 µl/ml as minimum inhibitory concentration of M. arvensis and P. betle essential oils, respectively. Furthermore, different combinations of M. arvenis and P. betle essential oils showed an additive effect on eliminating the fungal growth in vitro, probably by attacking distinct organelles of the yeast cells. Finally, kill-time analyses indicated that 80% - 90% of the tested strains were eliminated after 20 minutes of treatment with a combination of 1 µl/ml of M. arvensis and 0.5 µl/ml of P. betle essential oils. These data suggested that M. arvensis and P. betle essential oils (Eos) can be potential agents for formulating shampoo, cream or lotion to treat Malassezia-associated disease